Immunotherapy for Pemphigus: Present and Future - Yuan, Huijie; Pan, Meng; Chen, Hongxiang; Mao, Xuming (Frontiers in Medicine, 2022)
Pemphigus is a chronic and severe autoimmune bullous disease caused by autoantibodies targeting adhesion molecules between keratinocytes, which requires 2-3 years on average to manage the disease. To date, although Rituximab combined with short-term systemic glucocorticoids was accepted as a first-line therapy, systemic glucocorticoids still remain the primary therapeutic option for pemphigus patients, strikingly decreasing morbidity and mortality from pemphigus. However, novel therapeutic strategies are desirable due to the low efficacy in some subset of patients and the long-term severe adverse effects of traditional therapies. Notably, immunotherapy has proved to be encouraging for disease control or cure. Based on the current understanding of the immune mechanisms of pemphigus, we review the therapeutic targets and corresponding agents applied in practice or clinical trials. The goals of the novel treatments are to improve the quality of life of pemphigus patients by improving efficacy and safety, minimizing side effects, achieving fast disease control, or curing the disease.